Community Participation in Response to the Environmental Impact of PT Pusri’s Waste (A Study Palembang): JEL Classification: Q53, Q56, H83, R58, Z18 - Ilham Wahyudi; Isabella Isabella; Doris Febriyanti (Journal of Management and Administration Provision, 2026)
This study analyzes the perceptions of residents in administrative division I Ilir, Ilir Timur II District, Palembang, regarding the impact of industrial waste generated by PT. Pupuk Sriwijaya (Pusri), as well as the extent of community participation in the waste management process. Although Pusri has implemented Corporate Social Responsibility (CSR) programs and there have been communication efforts from local government authorities, issues related to waste impacts such as the odor of ammonia remain a concern, and the effectiveness of the mitigation efforts has not been fully perceived as significant by the community. A descriptive qualitative method was employed in this research, with data collected through in-depth interviews, observation, and documentation. The analysis was guided by Marschall’s (2006) theoretical framework on participation, which emphasizes three key indicators: the availability of community participation forums, community involvement in the process, and access to voice opinions. The findings reveal that although there is no formal forum specifically for waste-related issues, communication occurs through the neighborhood-level (RT/RW) hierarchy and the administrative division, which functions as the main facilitator. Community participation is primarily observed at the stage of expressing aspirations, but there remains an expectation for increased involvement throughout all stages of decision-making and oversight. While avenues for voicing opinions such as public discussions and hearings are available, transparency regarding the follow-up of decisions remains insufficiently perceived. These findings underscore the need to formalize participation forums, enhance comprehensive community engagement, and improve transparency from both the company and the government to achieve more participatory and responsive environmental governance.